Pengaruh Akad Al-Qardhul Hasan dan Akad Rahn dalam Produk Pembiayaan Syariah dalam Meningkatkan Pendapatan Mitra di BMT NU Cabang Kabat - Rahmat, Muhammad Habib; Faizal, Ahmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2023)
In research This study aims to definitively analyze the variables in the research that have been formulated previously, which are contained in the formulation of the problem. research that has been formulated previously, which is contained in the formulation of the problem that has been classified into several variable explanations, namely whether there is an has been classified into several variable explanations, namely whether there is an influence of Financing using AlQardhul Hasan and Financing using Rahn. which uses Rahn, on the increase in partner income (Y1). The population in this study were all partners of BMT NU Kabat Branch who have been or are using lasisma and pawn financing, while sampling using purposive sampling technique by considering certain factors, and determined as many as 102 respondents as the total sample. Data analysis tool data in this study using Multiple Linear Regression with hypothesis testing assisted using software (SPSS) Version 25. The results of the analysis show that financing using the Al-Qardhul Hasan Agreement has a significant effect on increasing partner income at BMT NU Kabat branch (Standardized Coefficients) of 0.495 (49.5%) with a positive value, Financing using the Rahn Agreement has a significant effect on increasing partner income at BMT NU Kabat branch, (Standardized Coefficients) of 0.465 (46.5%) is positive, The R quare value was obtained at 0.558, this shows that the increase in partner income was influenced by financing using al qardhul hasan contracts and rahn contracts amounting to 55.8%, while the remaining 44.2% was influenced by other variables not mentioned in this research.